Evaluation of single nucleotide polymorphisms in virulence genes of Mycobacterium tuberculosis as markers of lineages and sub-lineages in Tshwane region - Maningi, Nontuthuko Excellent (University of Pretoria, 2020)
Dissertation (MSc)--University of Pretoria, 2020.